2014
DOI: 10.1212/wnl.0000000000000238
|View full text |Cite
|
Sign up to set email alerts
|

Lower stroke risk with lower blood pressure in hemodynamic cerebral ischemia

Abstract: Objective: To determine whether strict blood pressure (BP) control is the best medical management for patients with symptomatic carotid artery occlusion and hemodynamic cerebral ischemia. Methods:In this prospective observational cohort study, we analyzed data from 91 participants in the nonsurgical group of the Carotid Occlusion Surgery Study (COSS) who had recent symptomatic internal carotid artery occlusion and hemodynamic cerebral ischemia manifested by ipsilateral increased oxygen extraction fraction. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
29
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(29 citation statements)
references
References 18 publications
0
29
0
Order By: Relevance
“…[1][2][3][4][5] The risk is likely increased if collateral supply is insufficient resulting in hemodynamic compromise. [6][7][8] Collateral pathways activated in response to ICAO have been categorized as either primary or secondary.…”
mentioning
confidence: 99%
“…[1][2][3][4][5] The risk is likely increased if collateral supply is insufficient resulting in hemodynamic compromise. [6][7][8] Collateral pathways activated in response to ICAO have been categorized as either primary or secondary.…”
mentioning
confidence: 99%
“…A study of a cohort predominantly composed of patients with carotid stenosis >75% or complete occlusion revealed that antihypertensive treatment was associated with significantly reduced recurrent stroke risk [7]. In patients with recently symptomatic CICAO and hemodynamic cerebral ischemia (Carotid Occlusion Surgery Study cohort), controlled hypertension (≀130/85 mm Hg) was associated with a reduced risk of subsequent ischemic stroke [18]. In clinical practice, physicians may be reluctant to treat hypertension to lower blood pressure targets because of concerns about reducing cerebral perfusion pressure in the setting of carotid high-grade stenosis or occlusion.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, this study provided Class III evidence by American Academy of Neurology criteria that control of hypertension ≀ 130/85 mm Hg is associated with a reduced risk of subsequent ipsilateral ischemic stroke in patients with recently symptomatic carotid occlusion and hemodynamic cerebral ischemia (increased OEF). 37 COSS patients with increased OEF represent the most extreme case of cerebral hemodynamic compromise. Nevertheless, lower blood pressures were associated with reduced, not increased, stroke risk.…”
mentioning
confidence: 99%